2021
DOI: 10.3390/diagnostics11081488
|View full text |Cite
|
Sign up to set email alerts
|

Common Biochemical and Magnetic Resonance Imaging Biomarkers of Early Knee Osteoarthritis and of Exercise/Training in Athletes: A Narrative Review

Abstract: Knee osteoarthritis (OA) is the most common joint disease of the world population. Although considered a disease of old age, OA also affects young individuals and, more specifically among them, those practicing knee-joint-loading sports. Predicting OA at an early stage is crucial but remains a challenge. Biomarkers that can predict early OA development will help in the design of specific therapeutic strategies for individuals and, for athletes, to avoid adverse outcomes due to exercising/training regimens. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 155 publications
(235 reference statements)
0
6
0
Order By: Relevance
“…Scoring and manual, semi-automatic, and fully automated quantitative systems are among the MRI knee tissue evaluation methods. Despite low tissue contrast and radiation exposure, CT is a reliable bone assessment technology with quick scanning time and good spatial resolution [71,72]. New studies have shown that machine learning has the ability to automate the diagnosis and prognosis of KOA, leading to increased accuracy, efficiency, and repeatability.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Scoring and manual, semi-automatic, and fully automated quantitative systems are among the MRI knee tissue evaluation methods. Despite low tissue contrast and radiation exposure, CT is a reliable bone assessment technology with quick scanning time and good spatial resolution [71,72]. New studies have shown that machine learning has the ability to automate the diagnosis and prognosis of KOA, leading to increased accuracy, efficiency, and repeatability.…”
Section: Diagnosismentioning
confidence: 99%
“…With ongoing advancements in model development, this technology could lead to novel therapeutic options. [71,73,74].…”
Section: Diagnosismentioning
confidence: 99%
“…A long list of biomarkers has been tested in OA for different purposes and listed in several recent reviews [7][8][9]. For the purpose of a concise description, we will only describe type II collagen and aggrecan, which are the main components of cartilage although other proteins may be of equal interest.…”
Section: Osteoarthritis -The Story Is Evolvingmentioning
confidence: 99%
“…However, the myriad of markers discovered so far, whilst helpful for understanding certain aspects of cartilage pathophysiology, paradoxically have also contributed to diverting rather than guiding physiatrists and other therapists in defining qualitatively and quantitatively the best interventional approach. A reason could be that many of these putative cartilage biomarkers are not as specific indicators of cartilage health as they should be [ 27 ]. Another aspect to bear in mind is that, pre-clinical and/or in vitro studies assessing knee joint cartilage deformation may not have the expected translational value in humans [ 28 ], pinpointing the need for further in vivo experimentation in humans [ 16 ].…”
Section: Introductionmentioning
confidence: 99%